ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM PEMBELIAN TABLOID NOVA DI KOTA PONTIANAK - Samsuddin Sam (Universitas Muhammadiyah Pontianak, 2013)
This study aims to determine the factors Cultural, Social, Personal and psychology affect consumer behavior in purchasing tabloid Nova in the city of Pontianak. This study is a survey method, whose population is all consumers tabloid Nova in Pontianak and 100 of whom were sampled were selected based on purposive sampling. Data analysis was performed with the Validity and Reliability Testing Instruments, factor analysis (Factor Analysis) which is used to determine the factors that influence consumers in the purchase Tabloid Nova in Pontianak. Test Bartlett's Test of Spehericity amounted to 795.181 less than the value α of 0.05 (5%), so Ho rejected and Ha accepted. Test Kaiser-Meyer-Olkin Measure of Sampling Adequacy amounted to 0,703 this value indicates the number is greater than required, amounting to 0.5-1.0 means of factor analysis suitable for use and there is a closeness between the variables in the population. Factors that influence the consumer's decision to buy tabloids Nova in Pontianak is reflecting social class, lifestyle, perceptions of news delivered and decision-making with the conscious, rational and deliberate, easily available and alternative options on the product, reading habits and customs in the neighborhood , the experience of families and benefits and will always buy. because of the influence of friends, adjust to the income and the drive to buy. The five factors that influence the consumer's decision to buy tabloids Nova in Pontianak has a cumulative percentage of variance (cumulative percentage of variance) of 67.948%. This shows that 5 (five) factors are able to explain the factors that influence the consumer's decision to buy tabloids Nova in Pontianak at 67.948%, while the remaining 31.239% is explained or influenced by other factors.Keywords: consumer behavior, cultural factors, personal, psychological